Designing theranostic radiopharmaceutical trials for uterine cervix cancer - Fabian, Denise; Buffington, Molly E.; Cagle, Brianna S.; Keefe, Steve M.; Schultz, Michael K.; Kunos, Charles A. (Frontiers in Oncology, 2026)
Designing and interpreting early phase trials of theranostic radiopharmaceuticals remains challenging because it is difficult to isolate effective levels of activity in enriched patient populations that would be worth following up in later-phase development. This study explores the known challenges and emerging opportunities for clinical research on patients with uterine cervical cancer. We identified eight randomized combination trials for advanced-stage uterine cervix cancer that were activated between 2011 and 2022 and tabulated their results to determine whether combinations were better than individual constituents and which suitable study population is best situated for the study of a new theranostic agent. In this overview, we discuss exploitable vulnerabilities and radiobiology of cancer-associated fibroblasts, as these stromal cells are targets for nuclear and therapeutic radiation medicine. We also discuss investigational drugs that hold promise for the theranostic treatment of persistent, recurrent, or metastatic uterine cervical cancer, including inhibitors of fibroblast activation protein-alpha and ribonucleotide reductase. In our expert opinion, the development of a theranostic radiopharmaceutical should pursue the eventual goal of being tested in a randomized phase II monotherapy setting.